The Comparative Study on Interpersonal Rejection Sensitivity, Death Anxiety and Quality of Life among Type 1 and Type 2 Diabetics - Batool, Sadia; Jaffri, Noreen (Annals of Human and Social Sciences, 2025)
A comparative study was conducted to examine the differences in interpersonal rejection sensitivity, death anxiety, and quality of life among individuals with type 1 diabetes and type 2 diabetes. The age range of participants was 18-40 years (N=300). The population was selected using purposive convenient sampling. The inclusion criteria for selecting participants were individuals diagnosed with diabetes and falling within the specified age range. Individuals with any other diagnosed psychological problems or taking psychotropic medication were excluded from the study. Data was collected using a consent form, demographic forms, the Interpersonal Rejection Sensitivity Scale (IRSS), the Death Anxiety Inventory-Revised (DAI-R), and the WHO Quality of Life Scale. The collected data was analyzed using the Social Science Statistical System (SPSS) with an unrelated t-test. The findings revealed that individuals with Type 1 diabetes reported significantly higher levels of death anxiety (p < 0.05, MD = 6.79) and interpersonal rejection sensitivity (p < 0.05, MD = 3.53) compared to those with Type 2 diabetes. However, no significant difference was found in the overall quality of life between the two groups (p = 0.705). The study’s implications included promoting social support and providing resources to help patients manage these factors and cope with negative emotions. The research findings were intended to assist in developing intervention plans and strategies to manage these psychological factors and improve the quality of life of individuals with diabetes.